POLA PENDISTRIBUSIAN PUPUK BERSUBSIDI BERDASARKAN PERATURAN MENTERI PERDAGANGAN NOMOR 4 TAHUN 2023 DI DESA KADUNDUNG KECAMATAN LATIMOJONG KABUPATEN LUWU - Pujiati, Shiva; Sabaruddin; Agustan (Datuk Sulaiman Law Review (DaLRev), 2024)
Subsidized fertilizer is a government program to increase agricultural productivity, consisting of various fertilizers: UREA, SP-36, ZA, NPK, and Organic fertilizer. This study aims to identify the distribution pattern of subsidized fertilizer based on the Regulation of the Minister of Trade No. 4 of 2023 in Latimojong District, Luwu Regency, as well as to review its distribution from the perspective of Islamic law. The research method used is qualitative research. The data sources consist of primary, secondary, and tertiary data. Data collection techniques include observation, interviews, and documentation. The data analysis techniques employed are data reduction, data presentation, and conclusion drawing. The study results show that the distribution pattern of subsidized fertilizer in Kadundung Village, Latimojong District, Luwu Regency, has not been optimal. This is due to recurring issues of fertilizer stock shortages, causing difficulties for farmers and forcing some of them to purchase non-subsidized fertilizer.